Analiza korespondencji w ocenie wiarygodności kredytobiorcy - Staniec, Iwona (Correspondence analysis in evaluation of the inborrower's creditworthiness, 2006)
The evaluation by use correspondence analysis of the credit risk has been presented in this article. It is based on data gained from "Gwarant" company for individual credits on purchase set. The test contained 4999 credit contracts. Among them 477 contracts (9.54 %) were not repaid and 4522 contracts (90.46 %) were paid off. Therefore a mischievousness was only 9.54 % in analysing test.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 256-262